The Effect of The Task Management System on The Employee's Performance of The Audit Board at The Head Office - Puspasari, Indah; Firdaus, Firdaus; Samboteng, Lukman (International Journal of Social Science, Education, Communication and Economics, 2024)
Task Management System is an application used by the Audit Board of Indonesia (BPK) with the main feature of monitoring daily attendance and daily employee activity reports. This application began to be used since the Covid-19 pandemic and is still used today. The aim of this research is to determine the effect of employee performance after using the application of a task management system. This research was conducted on employees of the Head Office of BPK with a sample of 255 employees. The independent variable in this research is the task management system while the dependent variable is employee performance. Variable measurement uses a Likert scale with a quantitative approach with the main data source through collecting questionnaires from BPK employees. This research uses SPSS version 26 software to analyze data. The results of the analysis show that the task management system has a significant and positive influence on employee performance. The contribution of the influence of the task management system variable is 46.3%, while the remaining 53.7% is influenced by other variables not tested in this research.